1977
DOI: 10.1103/physrevlett.38.23
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of SolidHe4Interfaces between Grafoil and High-Pressure LiquidHe4

Abstract: First-order phase transitions, such as solidliquid transitions, are commonly thought of and dealt with as purely bulk phenomena. It is appreciated that such transitions are probably usually nucleated in some fashion by impurities or walls, but details of this process have never before, to the authors' knowledge, been examined in careful detail. 1 What we report here are the first measurements of the continuous growth, on a microscopic scale, of a solid as the pressure approaches that of the solidification curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

1977
1977
1992
1992

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 12 publications
(3 reference statements)
3
14
1
Order By: Relevance
“…The nucleus is stabilized by an excess pressure, proportional to the interfacial tension between liquid and solid. Although the mechanisms are different, both these models [19,20] predict that excess pressure will be required to solidify 4 He in a disordered medium and compete with the mechanism described by Landau and Saam [18].…”
Section: By the Dashed Linementioning
confidence: 96%
See 1 more Smart Citation
“…The nucleus is stabilized by an excess pressure, proportional to the interfacial tension between liquid and solid. Although the mechanisms are different, both these models [19,20] predict that excess pressure will be required to solidify 4 He in a disordered medium and compete with the mechanism described by Landau and Saam [18].…”
Section: By the Dashed Linementioning
confidence: 96%
“…The model used by Landau and Saam [18] to describe the nucleation of solid 4 He assumes a local 4 He number density which depends on position. The number density is increased inside the attractive well created by the van der Waals potential of the substrate, increasing the local pressure at the substrate compared to the bulk.…”
Section: By the Dashed Linementioning
confidence: 99%
“…The initial stage is identical to that analyzed by Landau and Saam, 1 and we show in Fig. 3 (broken curve) the calculated thickness Z s of the solid layer 1 …”
Section: Role Of Substrate Symmetry In Nucleating Solid Heliummentioning
confidence: 96%
“…For example, Lawson 3~ detected preferentially oriented crystal growth of hcp solid 4He at a melting pressure of 85 atm on a specially prepared gold foil whose surface matched the solid, whereas previously no preferential orientation had been observed on copper. 31 Using a Grafoil substrate, Landau et al 32 found different results depending on whether the adsorbate is 3He or 4He. With 3He at temperatures between 30 and 320 mK they found no high-density phase if the melting curve was approached from an all-liquid state, but evidence for the existence of solid if the experiments started with solid present on the bulk melting curve.…”
Section: Discussionmentioning
confidence: 99%